Development and validation of a new prognostic immune–inflammatory–nutritional score for predicting outcomes after curative resection for intrahepatic cholangiocarcinoma: A multicenter study - Zhu, Jiang; Wang, Denghui; Liu, Chang; Huang, Rui; Gao, Fengwei; Feng, Xuping; Lan, Tian; Li, Hui; Wu, Hong (Frontiers in Immunology, 2023)
Background: Immune function, nutrition status and inflammation have been reported to exhibit a crucial effect on tumor initiation and progression. This retrospective multicentre cohort study aimed to comprehensively investigate the prognostic value and clinical relevance of immune, inflammatory and nutritional-related biomarkers, and to develop a novel prognostic immune-inflammatory-nutritional score (PIIN score) for Intrahepatic cholangiocarcinoma (ICC). Methods: Data of 571 consecutive patients (406 in the training set and 165 in the validation set) were collected from 4 large hepato-pancreatico-biliary centres for ICC patients who underwent surgical resection with curative intent between January 2011 and September 2017. We collected 12 blood biomarkers to develop PIIN score using the LASSO Cox regression model. The score's prognostic value was further assessed with validation datasets. Afterwards, the nomograms combining PIIN score and other clinicopathological parameters were developed and then validated in terms of the calibration curve, time-dependent AUC curves, and decision curve analysis (DCA). The Primary end points were overall survival (OS) and recurrence-free survival (RFS) from the day of primary resection of ICC. Results: On the basis of ALBI, NLR, PNI and SII biomarkers, PIIN score was developed and classified patients into high-risk and low-risk groups. Patients with high-risk scores had shorter OS (training set, p < 0.001; validation set, p = 0.003), and RFS (training set, p < 0.001; validation set, p = 0.002) than patients with low-risk scores. Higher PIIN score was also associated positively with larger tumor (≥5 cm), lymph node metastasis (N1 stage), multiple tumors, and higher tumor grade or TNM stage. Furthermore, high PIIN score was confirmed as a significant independent prognostic factor of OS and RFS in both training (p < 0.001) and validation cohort (p = 0.003), respectively. A PIIN-Nomogram for individualized prognostic prediction built by integrating PIIN score and clinicopathological variables yielded better predictive performance compared with TNM stage. Conclusions: PIIN score, as a novel immune-inflammatory-nutritional-related prognostic biomarker, is promising to distinguish the prognosis in resected ICC and can be a reliable prognostic tool to aid in personalized treatment. Our findings provide novel insights into the role of cancer-related immune disorders, inflammation, and malnutrition.